Wellness tourism: a bibliometric analysis approach - Martins, Patrícia Raquel Fernandes (2024)
An emerging field, wellness tourism can reduce stress levels and foster positive emotions, leading to a healthy balance of body, mind, and spirit and satisfying consumer experiences that enhance personal well-being. As a distinct subcategory of health tourism, it is often erroneously interchanged with medical tourism in the literature. Moreover, up to this point, no comprehensive review has assessed the effects of the COVID-19 pandemic on wellness tourism research. A bibliometric review was conducted to fill this gap. Data was collected in June 2023 through the Web of Science (WoS) database. The selection process encompassed articles published from January 2013 to June 2023. A total of 143 relevant peer-reviewed articles published in English-language journals were selected. Data were analyzed through evaluation techniques based on productivity and impact measures and relational techniques via mapping the results through VOSviewer software. Based on these findings, potential directions and suggestions for future research were proposed.